2008
DOI: 10.1007/bf03175572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lactic acid bacteria from kefir, molasses and olive brine as possible probiotics based on physiological properties

Abstract: A combination of eight strains comprising of Lactobacillus plantarum, Enterococcus faecium and Leuconostoc mesenteroides subsp. mesenteroides isolated from molasses, olives, beer and kefir were studied for growth at low pH and ox-bile resistance. pH neutralised cell-free supernatants from 24-h-old cultures inhibited the growth of Enterococcus faecium, Lactobacillus sakei, Lactococcus lactis subsp. lactis, Listeria innocua and Listeria ivanovii subsp. ivanovii. Good growth was recorded in MRS broth supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 46 publications
5
31
1
Order By: Relevance
“…The interference of anti‐inflammatory drugs containing diclofenac on the viability of LAB detected in this study (Table 2) was also reported in other studies. Todorov and Dicks (2008) observed that this drug inhibited the growth of Lact. plantarum ST8KF and ST341LD, Ent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interference of anti‐inflammatory drugs containing diclofenac on the viability of LAB detected in this study (Table 2) was also reported in other studies. Todorov and Dicks (2008) observed that this drug inhibited the growth of Lact. plantarum ST8KF and ST341LD, Ent.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation is an important feature for biofilm formation. However, co‐aggregation between LAB and other cells, especially L. monocytogenes , may be considered a positive characteristic, as it is one of the steps required for the elimination of nondesirable strains from the GIT (Todorov and Dicks 2008). Auto‐aggregation and co‐aggregation are strain‐specific and most probably involve species‐specific surface proteins.…”
Section: Introductionmentioning
confidence: 99%
“…; Foulquié‐Moreno et al . ; Todorov and Dicks ). However, their role as probiotics is still controversial because of their increased association with nosocomial infections and harbourage of multiple antibiotic‐resistant genes, transmissible by conjugation to nonpathogenic micro‐organisms (Franz et al .…”
Section: Introductionmentioning
confidence: 97%
“…Aggregation plays an important feature in biofilm formation; however, co‐aggregation with pathogens may be considered as a positive characteristic. Thus, aggregation is one of the steps required for the elimination of pathogenic or nondesirable organisms from gastrointestinal tract regions (Todorov & Dicks, ). Bacterial aggregation between microorganisms of same species (auto‐aggregation) or between genetically different species (co‐aggregation) is of considerable importance in ecological niches, especially in human gut regions.…”
Section: Resultsmentioning
confidence: 99%